ANALISIS KETEPATAN INSTRUMEN KEBIJAKAN PENGELOLAAN SAMPAH BERBASIS REDUCE REUSE RECYCLE (3R) DI DESA ADIKARTO KECAMATAN MUNTILAN KABUPATEN MAGELANG - Muhammad Rafli Anggara1; Retno Sunu Astuti; R Slamet Santoso (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
Garbage is a public problem in Indonesia, including in Magelang Regency by becoming one of the waste emergency areas. Adikarto Village, Muntilan District, is one of the areas that is less than optimal in terms of the quantity of waste produced and goes to the Pasuruan TPA. This study aims to analyze the determination of the use of mixed policy instruments in the reduce, reuse, and recycle (3R)-based waste management policy in Adikarto Village, Muntilan District, Magelang Regency. The research method used is descriptive qualitative with data collection techniques in the form of interviews, observations and documentation. This research uses Howlett & Ramesh's theory of policy instruments and Van Metter & Van Horn's theory of policy implementation. The results of this study indicate that the use of mixed policy instruments is appropriate because to implement waste management policies it is necessary to intervene by local governments so that policy implementation is truly optimal. Factors driving the accuracy of this instrument include subsidies, user fees, policy standards and targets, and adequate resources. While the inhibiting factors can be identified from the dissemination of information, auction of rights, communication, organizational characteristics, attitudes of the implementers, as well as environmental conditions.